Sensitivity and Specificity of High-Resolution Computer Tomography in the Diagnosis of COVID-19 Infections - Lalchan, Subita; Kushwaha, Niraj (Nepalese Journal of Radiology, 2021)
Introduction: The goal of this study is to find the sensitivity and specificity of High resolution computed tomography (HRCT) of the chest in diagnosing COVID-19 infection using Reverse Transcription Polymerase Chain Reaction (RT-PCR) as a gold standard. Methods: All patients clinically suspected of having COVID 19 infection who had undergone both RT PCR test and HRCT chest were included in the study. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of HRCT chest in diagnosing COVID 19 infection were calculated considering RT-PCR as the gold standard test. Results: A total of 100 patients were included in the study. The mean age was 55.68 years. HRCT chest showed 92.85 % sensitivity, 68.75 % specificity, 93.97 % PPV, 64.7 % NPV and 89 % diagnostic accuracy in the detection of COVID-19 infection. Conclusion: HRCT scan of the chest shows high sensitivity and specificity for the diagnosis of COVID-19 pneumonia. It is a fast diagnostic test and also helps in grading the severity of pneumonia thus in further management.